Homo sapiens to homo digitalis: Understanding the economy of NEP 2020 - Das, Debabrata (Economic and Political Weekly)
Through a systematic call for massive corporate investment in the education sector and a greater emphasis on the online mode, education sector is manoeuvring the revival of the enfeebled capitalist system. To analyse this interrelationship, we require studying the complex network of power and hegemony within a given society.- Reproduced